(untitled) (Jurnal Mekanikal, 2018)
The guided wave structural monitoring system relies heavily on the known guided wave behaviour in the waveguides. These behaviours are commonly obtained from the dispersion curves. For isotropic plates, analytical expression for the dispersion curves exist. The same dispersion curves can be obtained experimentally or by using finite element method (FEM) with fine meshes. Hence, the FEM simulation approach requires high computation cost. A preliminary study is made in this contribution to simplify the simulation of solid isotropic plate as simulation of plates having trussed structures. By doing so, the computational requirement in the FEM simulation would greatly be reduced. To gauge the effectiveness of the proposed approach, the dispersion curves of plate having trussed structures is obtained from the FEM simulation. The result is then used to find the connection between the solid plate and the plate having trussed structures and the possibilities of simplifying the FEM simulation. The comparison made with analytical result revealed that the best approximation comes from cross geometry truss structure. However, good correlation is observed only for anti-symmetric mode.